The Influence of the Mekongga Traditional House on the Development of Sustainable Tourism in the Regency of Kolaka - Sopiandy, Dede; Rahmat, Alibin; Ramly, Amisbah; Hariyadi, Slamet; Murdiansyah, Eko Bambang (SAINTIS Publishing, 2025)
Based on a study conducted in Kolaka Regency, Southeast Sulawesi, this research explores the potential of the Mekongga Traditional House as a driver of sustainable tourism development. The study employs a mixed-methods approach that integrates quantitative and qualitative data to provide a comprehensive understanding of visitor perceptions and stakeholder perspectives. Quantitative data were collected through surveys administered to 44 respondents, while qualitative insights were obtained through interviews with government officials and local tourism actors involved in the management and promotion of the site. The findings reveal that visitors to the Mekongga Traditional House are predominantly female (72.7%) and under the age of 20 (63.6%), indicating a strong appeal among younger demographics. A majority of respondents (63.6%) reported satisfaction with the existing facilities, suggesting that the site has met basic visitor expectations. Social media emerged as the primary source of information about the destination (45.5%), highlighting its importance as a promotional tool. In terms of impact, the social dimension of the traditional house was perceived positively by most respondents (54.5%), reflecting its role in preserving cultural identity and fostering social interaction. However, perceptions of environmental impact were more varied, with a considerable proportion of respondents expressing neutral views (38.6%), indicating the need for improved environmental management. Overall, the Mekongga Traditional House represents a valuable cultural asset with strong potential to support sustainable tourism development. To maximize this potential, the study recommends increasing environmental cleanliness awareness, enhancing tourism facilities, strengthening social media-based promotion, and encouraging active community participation in tourism management.